Focused ion beam micromachining of mems - Ali, Mohammad Yeakub (2008)
This paper discussed focused ion beam micro nano machining to fabricate MEMS (microelectromechanical systems) such as optical elements, trimming of atomic force microscope (AFM) tip, nanopillar, micromilling tool, microcavity for replication is discussed. The trimmed AFM tip was tested in measurement and imaging of high aspect ratio nanopillars where higher accuracy and clarity were observed. Micromilling tool fabricated using FIB sputtering was used in micromilling with desktop milling machine to machine microchannels. Cavities of hair-sized microgear were sputtered using FIB with submicrometer accuracy and nanometric leveled surface finish. Microcavities were used in microinjection molding for mass production of polymer microcomponents. The overall sizes of these microcomponents were few tens to few hundreds micrometers. The replicated microcomponents were inspected with scanning electron microscope where faithful duplication of accuracy and surface texture of the cavity was observed. These fabricated microcomponents have potential application in biomedical and other microelectromechanical systems.